LITERASI DIGITAL BERETIKA UNTUK GENERASI Z: PENGABDIAN MASYARAKAT DALAM SEMINAR DARING TENTANG BISNIS BERKELANJUTAN - Astuti, Andarweni; Saputra, Deri (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
Generation Z faces challenges in conducting ethical digital businesses amidst rapid technological advancements. Many of them are tempted to gain instant profits without considering moral and security aspects. The online seminar "Classy Success with Profitable, Ethical, and Safe Business Principles" was conducted as part of a community service program to enhance digital literacy and business ethics among young entrepreneurs. The primary goal of this activity was to equip participants with a deeper understanding of business transparency, marketing ethics, and customer data protection within the digital ecosystem. This seminar utilized interactive presentations, group discussions, and case studies to engage participants effectively. An evaluation conducted through surveys indicated a significant increase in participants' understanding of key aspects of ethical digital business. These results suggest that the seminar effectively provided applicable insights for Generation Z in developing sustainable and responsible technology-based businesses. Similar activities are expected to continue to strengthen a healthy and ethical digital business ecosystem.